The Influence Of Promotion And Price On Purchasing Decisions For Toyota Car - Nataliani, Nataliani; Ningsih, Nonita Kristya; Soejono, Fransiska (Universitas Pamulang, 2023)
The purpose of this study is to see whether promotion and price have an effect on purchasing decisions. Toyota is the largest car manufacturer in the world. The population of this study are consumers who know and have used or are using Toyota products in 2023. The sampling method uses non-probability sampling, namely the purposive sampling method (judgment sampling). the sample in this study were 94 respondents. Data was collected using an online questionnaire (google form) distributed via social media. Based on the findings of this study, promotion and price have a positive and significant effect on purchasing decisions for toyota cars.